Alexithymia and alcohol: The roles of punishment sensitivity and drinking motives - Lyvers, M.; Hasking, Penelope; Albrecht, B.; Thorberg, F. (Routledge, 2012)
Alexithymia refers to difficulties identifying and describing feelings. It is suspected of being a risk factor for problematic drinking, an idea examined by this study. In 178 women and 84 men alexithymia was associated with male gender, coping motives for drinking and sensitivity to punishment. Individuals with alexithymia reported stronger coping motives and sensitivity to punishment compared to those with borderline or no alexithymia. Path analysis indicated that the relationship between the alexithymia dimension difficulties identifying feelings and coping motives was mediated by sensitivity to punishment, and the relationship between sensitivity to punishment and risky drinking was mediated by coping motives. These results suggest that alcohol may be used by individuals with alexithymia to help them cope with anxiety or other negative affect.